Original paperEffects of leflunomide treatment on pro-inflammatory mediators in rheumatoid arthritis patients - Targońska-Stępniak, Bożena; Chudzik, Dariusz; Dryglewska, Magdalena; Majdan, Maria (Reumatologia/Rheumatology, 2007)
The objective of the study was to investigate the effects of LEF on disease activity and pro-inflammatory mediators during the first 6 months of therapy. We analyzed the course of LEF therapy of 37 RA patients (pts). In 31 pts (83.3%) LEF treatment was continued for at least 6 months; the therapy was interrupted in 6 pts (16.2%) due to adverse events or non-satisfactory clinical effect. Clinical and laboratory data were determined at weeks 0, 4, 12 and 24: disease activity score (DAS 28), C reactive protein (CRP), erythrocyte sedimentation rate (ESR), haemoglobin (HB), erythrocyte (ERY) and platelet (PLT) count, serum concentrations of albumin, interleukin 6 (IL-6), soluble interleukin 6 receptor (sIL-6R), serum amyloid A (SAA) and osteoprotegerin (OPG). The mean value of DAS28 decreased constantly after treatment. During the follow-up mean values of CRP, ESR and PLT count significantly decreased and mean concentrations of albumin, Hb and ERY count significantly increased between week 0 and consecutive weeks. The mean serum concentration of IL-6 decreased significantly between week 0 and weeks 4 and 12 (p<0.01). The mean serum concentration of sIL-6R decreased significantly between weeks 0 and 4 (p=0.03). SAA concentrations were very high in our pts at baseline and decreased constantly in the following weeks 4, 12 and 24 (p<0.01). OPG concentrations were higher at week 4, 12 and 24 with statistical significance between weeks 0 and 4 (p<0.05). Leflunomide therapy in RA pts induces clinical improvement which is connected with significant reduction of SAA and pro-inflammatory cytokine concentrations.